Perspectives of Healthcare Providers in Maternal and Child Health Services in Bokeo Province, Lao People’s Democratic Republic: A Qualitative Study - Kapheak, Krissana; Theerawasttanasiri, Nonthaphat; Khumphoo, Potchara; Sriwongphan, Rungrasami; Ritthimon, Wanchalerm; Chayaseng , Chansy; Bounmaseng, Phouangphet; Pangsri, Ninrat; Ngampradit, Yuparat; Wungrath, Jukkrit (Journal of Population and Social Studies [JPSS], 2023)
In Bokeo province, Lao People’s Democratic Republic, the high rates of poverty and poor health outcomes are striking. According to data collected from the Lao government, the area has a high mortality rate among mothers and children under five years old. Consequently, there is an urgent need for significant enhancements in maternal and child health (MCH) services. This study aims to investigate the perspectives of healthcare providers on the MCH situation, difficulties, challenges, and potential solutions for the growth and implementation of MCH services. We conducted in-depth interviews with 45 healthcare providers from varying healthcare system levels using qualitative methods. The key findings are as follows: Healthcare providers demonstrate a strong understanding of MCH policies, acknowledgment of national objectives, and dedication to personal growth. However, significant obstacles exist, including access barriers for ethnic minorities, transportation complications, inadequate healthcare personnel, and insufficient equipment and infrastructure. Healthcare providers have also indicated a need for more training and opportunities for professional development to improve MCH outcomes. To enhance MCH outcomes in Bokeo province, addressing these challenges and supporting healthcare providers in their quest for self-improvement is essential. The findings of our study can aid in creating targeted interventions and policies to improve MCH outcomes in Bokeo province and similar regions. By focusing on critical areas such as antenatal care, skilled birth attendance, postnatal care, immunizations, nutrition, family planning, health education, and access to healthcare, we can strive towards improved health outcomes and reduced mortality rates.